2003
DOI: 10.1017/s0031182003004074
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Toxocara canis in pigs receiving a single or multiple infection

Abstract: The population dynamics of Toxocara canis in pigs, and their immune response to a primary and a challenge infection, were studied by parasitological, haematological and serological parameters. Seventy pigs were divided into 4 groups; 35 pigs received a primary infection (group A), 15 pigs received both a primary and a challenge infection (group B), 15 pigs received the challenge infection only (group C), and 5 pigs served as helminth-free controls (group NC). A dose of 50,000 eggs was administered for the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
(38 reference statements)
5
24
0
Order By: Relevance
“…Our results also agree with previous observations of macroscopic lesions in pigs inoculated with T. canis 4,10,17,20 . White spots on the liver were also observed by TAIRA et al 24 . One notable difference between our study and previous research that inoculated T. canis , was the absence of the typical granulomatous reaction in our sample.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Our results also agree with previous observations of macroscopic lesions in pigs inoculated with T. canis 4,10,17,20 . White spots on the liver were also observed by TAIRA et al 24 . One notable difference between our study and previous research that inoculated T. canis , was the absence of the typical granulomatous reaction in our sample.…”
Section: Discussionsupporting
confidence: 59%
“…In pigs, DONE et al 4 reported that T. canis larvae have been previously shown to migrate primarily to the liver and lungs; HELWIGH et al 10 and TAIRA et al 24 , to the lungs and lymph nodes; SOMMERFELT et at. 20 observed to the lymph nodes, liver, and lungs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental infections with Toxocara canis have shown that pigs are suitable hosts and that larva migrans can occur with the liver and lungs being favoured sites for the larvae during early infection stages [2,3]. To the best of our knowledge there are no published cases of naturally infected pigs with Toxocara cati larva migrans, although pigs are listed as a suitable paratenic host [4] and T. cati eggs have been detected in the faeces of fattening pigs [5].…”
mentioning
confidence: 99%